Applied groundwater modeling : simulation of flow and advective transport - Anderson, Mary P. (Academic Press, 1992)
Creating numerical groundwater models of field problems requires careful attention to describing the problem domain, selecting boundary conditions, assigning model parameters, and calibrating the model. This unique text describes the science and art of applying numerical models of groundwater flow and advective transport of solutes. Key Features * Explains how to formulate a conceptual model of a system and how to translate it into a numerical model * Includes the application of modeling principles with special attention to the finite difference flow codes PLASM and MODFLOW, and the finite-element code AQUIFEM-1 * Covers model calibration, verification, and validation * Discusses pathline analysis for tracking contaminants with reference to newly developed particle tracking codes * Makes extensive use of case studies and problems.